2018
DOI: 10.3892/ol.2018.7800
|View full text |Cite
|
Sign up to set email alerts
|

HSPA12B overexpression induces cisplatin resistance in non-small-cell lung cancer by regulating the PI3K/Akt/NF-κB signaling pathway

Abstract: Abstract. Although cisplatin (CDDP) is widely used for non-small-cell lung cancer (NSCLC) treatment, resistance remains a major problem that restricts its efficacy. Therefore, identification of drugs that reverse or prevent resistance to CDDP in NSCLC has been a focus of a number of studies. The results of the present study revealed the effect of heat shock protein family A member 12B (HSPA12B) overexpression on chemoresistance in A549 cells in vitro. The effect of HSPA12B overexpression on chemoresistance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Previous studies found that HSPA12B is a potential activator of PI3K/Akt/mTOR signaling in endothelial cells and in some cancer cells. 23 , 24 Actually, activation of the PI3K/Akt/mTOR signaling is critical for M2 polarization of macrophages. 25 Therefore, we further assessed whether exogenous HSPA12B could activate the PI3K/Akt/mTOR signaling in macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that HSPA12B is a potential activator of PI3K/Akt/mTOR signaling in endothelial cells and in some cancer cells. 23 , 24 Actually, activation of the PI3K/Akt/mTOR signaling is critical for M2 polarization of macrophages. 25 Therefore, we further assessed whether exogenous HSPA12B could activate the PI3K/Akt/mTOR signaling in macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic mice overexpressing HSPA12B subjected to xenograft lung tumor models have significantly upregulated expression of VEGF and angiopoietin-1 and enhanced eNOS phosphorylation compared with wild-type counterparts. 26 Its upregulation induces chemo-resistance in non-small-cell lung cancer 24 and cervical squamous cell carcinoma. 27 However, as a modulator of immune responses in endothelial cells, its functional role in tumor immune microenvironment has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT/NF-κB pathway affected the expression of Bcl-2 and caspase-3, which was cleaved by apoptotic proteins. These alterations regulated NSCLC cell growth and apoptosis to promote MDR 70 . Abnormal activation of the PI3K/AKT/NF-κB signaling pathway also regulated the expression of P-gp to achieve MDR, which is discussed in the following sections 23 .…”
Section: Pi3k/akt/nf-κbmentioning
confidence: 99%
“…The AKT/NF-κB signaling pathway is constitutively activated in several types of cancer, including NSCLC ( 6 ). Furthermore, the high AKT/NF-κB activation has also been demonstrated as a key mechanism of acquired cisplatin resistance by increasing the threshold for cell death induction ( 8 , 9 ). Exposure to cisplatin activates AKT/NF-κB signaling, which consequently induces the expression of NF-κB target genes, including anti-apoptotic genes and genes involved in cell survival, such as Bcl-xL and survivin.…”
Section: Introductionmentioning
confidence: 99%